388 Efficacy of individualised starting dose (ISD) and fixed starting dose (FSD) of niraparib per investigator assessment (IA) in newly diagnosed advanced ovarian cancer (OC) patients. (4th December 2020) - Peen, Ulla; Graybill, Whitney; González-Martin, Antonio; O'malley, David; Baurain, Jean-François; Prendergast, Emily; Follana, Philippe; Braicu, Elena I; Gupta, Divya; Monk, Bradley J
Abstract : Introduction: Niraparib is a poly(ADP-ribose) polymerase inhibitor approved for maintenance treatment of patients with newly diagnosed or recurrent OC that responded to platinum-based chemotherapy and treatment in heavily-pretreated recurrent OC. Here we report efficacy in patients receiving the FSD and ISD in the PRIMA/ENGOT-OV26/GOG-3012 trial (NCT02655016 ). Methods: This double-blind, placebo-controlled, phase 3 study randomised 733 patients to receive niraparib or placebo for 36 months or until disease progression/toxicity. A protocol amendment introduced ISD: 200 mg in patients with body weight <77 kg or platelets <150, 000/µL, or 300 mg in all others. The primary endpoint was PFS by blinded independent central review (BICR). IA PFS was a sensitivity analysis. At the primary analysis data cut, follow-up was 11.2 months and 17.1 months in the ISD and FSD subgroups, respectively. An ad hoc analysis of IA PFS was performed using an updated data cut with additional 6 months follow-up. Results: BICR and IA PFS were highly concordant in the overall population. Efficacy of niraparib based on IA PFS in FSD vs ISD subgroups for each data cut were similar (table 1 ). Dose interruptions, modifications, and haematologic toxicity were lower with the ISD. Exposure–response data supported the clinical data. Conclusion: The 200- or 300-mg ISD by baseline body weight and platelet counts demonstrated comparable efficacy while improving the safety profile of niraparib. Use of this regimen for first-line maintenance of advanced OC patients is approved by the US FDA. Disclosures: Funded by: GlaxoSmithKline NCT: NCT02655016 Encore statement: This data is presented on behalf of the original authors with their permission. Presented at the International Gynecologic Cancer Society (IGCS) Annual Global Meeting, September 10–13, 2020, Virtual. Dr. González-Martín reports personal fees and non-financial support from AstraZeneca; Grant and personal fees from GSK, Clovis Oncology, Roche Holding AG, Merck & Co., Inc., Genmab, INMUNOGEN, Pharma Mar, S.A., and Oncoinvent AS. Dr. Graybill reports personal fees from GSK. Dr. O'Malley reports personal fees from Immunogen, Eisai, Agenus, GSK : Consultant/Advisory Board for Clovis, Ambry, Abbvie, Janssen/J&J, Regeneron, Novacure, Myraid Genetics, Tarveda, Amgen, VentiRx, Array Biopharma, EMD Serono, Ergomed; Steering committee for Genentech/Roche and Merck; Institutional funding from Ajinomoto Inc, Ludwig Cancer Research, Stemcentrx, Inc, CERULEAN PHARMA, GOG Foundation, BMS, Serono Inc, TRACON Pharmaceuticals, Yale University, New Mexico Cancer Care Alliance, INC Research, Inc., Inventiv Health Clinical, Iovance Biotherapeutics, Inc, and PRA International. Dr. Monk reports consulting and advisory role at Merck, GSK, Roche/Genentech, AstraZeneca, Advaxiz, Cerulean Pharma, Amgen, Immunogen, NuCana BioMed, Clovis Oncology, Pfizer, Mateon Therapeutics, Precision Oncology, Perthera, Abbvie, Myriad Pharmaceuticals, Incyte, VBL Therapeutics, Takeda, Samumed, Oncomed, OncoSec, ChemoID, Geistlich Pharma, Eisai and Chemocare; Speakers' bureau at Roche/Genentech, AstraZeneca, Janssen, Clovis Oncology and GSK; Honoraria from Merck, GSK, Roche/Genentech, AstraZeneca, Advaxis, Immunogen, NuCana BioMed, Clovis Oncology, Pfizer, Mateon Therapeutics, Precision Oncology, Pethera, Abbvie, Myriad Pharmaceuticals, Incyte, Janssen, Amgen, Genmab, Samumed, Takeda, VBL Therapeutics, Puma Biotechnology, Immunomedics, Conjupro Biotherapeutics, Agenus, OncoQuest, ChemoID, Geistlich Pharma, Eisai and Chemocare; and Research funding from Novartis, Amgen, Genentech, Lilly, Janssen, Array BioPharma, GSK, Morphotek, Pfizer, Advaxis, AstraZeneca, Immunogen, Regeneron, and Nucana. Drs. Peen, Yap, Baurain, Pisano and Baumann have nothing to disclose. Dr. Gupta is an employee of GlaxoSmithKline.